2021
DOI: 10.1115/1.4049601
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Ether and Liquefied Petroleum Gas Co-Fumigation and Oxidation Catalyst Exhaust Aftertreatment: A Synergy for Improvement of Thermal Efficiency and Emissions in a Dual-Fuel Engine

Abstract: Gaseous hydrocarbon (HC) fuels or alcohols can partially replace diesel in compression ignition engines through the dual-fuel mode of combustion. However, such dual-fuel mode faces the challenges of high carbon monoxide (CO) and unburnt HC emissions and low thermal efficiency, particularly at low loads. The objective of this study is to achieve dual-fuel engine thermal efficiency and emissions better than those of a diesel mode while utilizing alternative fuels. A new approach consisting of a combined strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Various injection strategies [3][4][5][6][7][8], engine operation conditions [9][10][11] and fuel blends [12][13][14][15][16][17][18] of DME-fueled engines have been investigated. Youn et al [8] showed that the use of DME was associated with a higher pressure and earlier increase in the Energies 2022, 15,1912 2 of 11 heat release rate (HRR) compared to diesel, because the ignition delay was shorter, the vaporization characteristics were more favorable, and the cetane number was higher.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various injection strategies [3][4][5][6][7][8], engine operation conditions [9][10][11] and fuel blends [12][13][14][15][16][17][18] of DME-fueled engines have been investigated. Youn et al [8] showed that the use of DME was associated with a higher pressure and earlier increase in the Energies 2022, 15,1912 2 of 11 heat release rate (HRR) compared to diesel, because the ignition delay was shorter, the vaporization characteristics were more favorable, and the cetane number was higher.…”
Section: Introductionmentioning
confidence: 99%
“…This enabled reductions in nitrogen oxide (NO x ) and soot emissions when the combustion temperature is decreased during the combustion process. As the physical properties of DME are similar to those of liquefied petroleum gas (LPG), DME has been blended successfully with diesel [12], LPG [13], biodiesel [16,17], gasoline [18] and other fuels [14,15].…”
Section: Introductionmentioning
confidence: 99%